A novel method for life estimation of power transformers using fuzzy logic systems: An intelligent predictive maintenance approach - Naeem Muhammad Farhan; Hashmi Khurram; Kashif Syed Abdul Rahman; Khan Muhammad Mansoor; Alghaythi Mamdouh L.; Aymen Flah; Ali Samia G.; AboRas Kareem M.; Ben Dhaou Imed (FRONTIERS MEDIA SA, 2022)
Power transformers are a fundamental component of the modern power distribution network. The fault-free operation of step-up and step-down transformers is of prime importance to the continuous supply of electrical energy to the consumers. To ensure such efficient operation, power distribution companies carry out routine maintenance of distribution transformers through preplanned schedules. The efficacy of such maintenance depends on a proper understanding of the transformer and its components and efficient prediction of faults in these components. There are several components whose condition can be studied to predict transformer failures and therefore the overall health of a transformer. These include transformer windings, insulations, transformer oil, core insulations, and ferromagnetic cores. This work develops a new, simplified fuzzy logic-based method to predict the health of a transformer by taking into account the state of several individual components. Case studies are used to demonstrate the efficacy of the developed method.